Phytochemical and biological study of some rumex species ( Rumex vesicarius ) family polygonaceae - Marwa Yehia Elharriry; Kamilia Fouly Taha; Nadia Sokkar; Seham Elhawary (Cairo : Marwa Yehia Elharriry, 2012)
The present study was designed to investigate the bioactive compounds in extracts of Rumex vesicarius L. ( Polygonaceae ) , a wild edible herb grwing in Egypt . Ethyl acetate and n - butanol fractions of leaves of R. vesicarius were conducted by HPLC - PDA - MS / MS - ESI in the negative mode to analyze phenolics content
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacognosy
Issued also as CD
Keywords: Hepatoprotection; Nutritive; Phenolics